Analysis of Murabahah Financing for Customers Who Die Before the Maturity: Study of KBSU Tikung Lamongan - Buana, Miftahal Anjarsabda Wira; ZA, Moh. Ah. Subhan; Jannah, Nur (Majapahit Journal of Islamic Finance and Management, 2025)
Financing customers who die before maturity but still have financing is one of the situations that occur in KBSU Lamongan, savings from depositors used for financing are naturally the responsibility of the bank in running its business. Based on the background above, the researcher is interested in raising the title "Analysis of Murabah Financing for Customers Who Die Before Maturity". This study uses a qualitative research method with a descriptive analysis approach. Qualitative is used because the main objective of this study is to reveal, explain and interpret the KBSU Strategy in handling murabahah financing for customers who die before maturity. Handling financing for customers who die is by taking an emotional approach to the heirs where the bank will convey that the parents concerned have made a loan. or in this regard, the heirs who inform the bank verbally that the customer who has financing has died, then the family is responsible for the financing by attaching a statement of no insurance signed by the family to prevent losses and minimize the risk if the financing customer dies. The obstacles that banks usually face in handling deceased customers are the circumstance factor, where the customer has not been able to report because the heirs are still grieving, the negligence factor, namely the slow confirmation from the family, this is negligence on the part of the family itself, namely delaying reporting and the slow document fulfillment factor.